A Stability-Indicating Assay for Tetrahydrocurcumin-Diglutaric Acid and Its Applications to Evaluate Bioaccessibility in an In Vitro Digestive Model - Nattapong Jongjitphisut; Worathat Thitikornpong; Wisut Wichitnithad; Thanundorn Thanusuwannasak; Opa Vajragupta; Pornchai Rojsitthisak (Molecules, 2023)
A simple and reliable ultra-high-performance liquid chromatographic (UHPLC) method was developed and validated for determination of tetrahydrocurcumin diglutaric acid (TDG) and applied for evaluation of its bioaccessibility. The analytical method was validated to demonstrate as a stability-indicating assay (SIA) according to the ICH Q2(R1) guidelines under various force degradation conditions including thermal degradation, moisture, acid and base hydrolysis, oxidation, and photolysis. The developed chromatographic condition could completely separate all degradants from the analyte of interest. The method linearity was verified in the range of 0.4–12 μg/mL with the coefficient of determination (r2) > 0.995. The accuracy and precision of the method provided %recovery in the range of 98.9–104.2% and %RSD lower than 4.97%, respectively. The limit of detection and quantitation were found to be 0.25 μg/mL and 0.40 μg/mL, respectively. This method has been successfully applied for the bioaccessibility assessment of TDG with the bioaccessibility of TDG approximately four fold greater than THC in simulated gastrointestinal fluid. The validated SIA method can also benefit the quality control of TDG raw materials in pharmaceutical and nutraceutical development.